The Effects of Exercise on Working Memory in Adults - Yustin, Annisa; Irfana, Laily; Indrawati, Nina Devi; Prasetya, Era Catur; Alwi, Muhammad Najib Mohamad (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2024)
Background: Working memory (WM) is a crucial element of cognitive function. A reduction in WM capacity may adversely impact the quality of life and elevate the risk of developing neurodegenerative diseases in the future. Presently, no established medication can effectively prevent cognitive decline. Objective: Over the past decade, numerous research articles have investigated the consequences of exercise on cognitive function, mainly focusing on WM in adults.Methods: Critical reading of several pieces of literature discussing exercise's effect on WM. A search for scientific articles was conducted using online databases such as PubMed and Google Scholar.Results: Exercise improves WM through neuroplasticity. Post-exercise improvement in WM can be seen in every age studied. Exercise can reduce the risk of neurodegenerative diseases by maintaining the integrity of the substantia alba.Conclusion: Exercise emerges as a cost-effective strategy accessible to many individuals. It can potentially prevent declines in cognitive function, positively impacting both present and future quality of life.